Expression patterns of bone morphogenetic protein 7 (BMP7) and its prognostic roles in neuroblastoma: An integrated bioinformatics analysis - Haiwei Wang; Xinrui Wang; Liangpu Xu (PLoS ONE, 2026)
Background Bone morphogenetic proteins (BMPs) are associated with the prognosis of various types of adult cancers. However, the expressions and prognosis of BMPs in pediatric neuroblastoma remain unclear. Methods Six publicly available neuroblastoma cohorts were downloaded for bioinformatics analysis. The prognosis of BMPs in neuroblastoma was determined using cox regression analysis and Kaplan-Meier survival analysis. Results Our study revealed that, compared to other BMP family members, BMP1, BMP7 and BMP8B were highly expressed in neuroblastoma. However, only BMP7 was associated with the prognosis of neuroblastoma in all six neuroblastoma cohorts. Higher BMP7 expression was associated with the shorted event free survival and overall survival of neuroblastoma. The prognosis of BMP7 in neuroblastoma was independent of age and MYCN amplification. The expressions of BMP7 were higher in neuroblastoma patients with MYCN amplification or age ≥ 18months or in stage 4 neuroblastoma. Moreover, higher BMP7 was associated with the shorted event free survival and overall survival of MYCN amplified or stage 4 neuroblastoma. At last, we found that breast cancer metastasis suppressor 1 (BRMS1) was correlated with BMP7 expression. However, in contrast with the suppressor role of BRMS1 in adult cancers, BRMS1 was significantly associated with the unfavorable clinical outcomes of neuroblastoma. Overall, our analysis the demonstrated correlations between BMPs and clinical features of neuroblastoma and provided unique therapeutic targets for neuroblastoma treatments. Conclusions BMP7 was a prognostic maker of neuroblastoma.